2018
DOI: 10.1016/j.technovation.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of political connections and managerial overconfidence on R&D intensity in China's large-scale private sector firms

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 54 publications
1
42
1
Order By: Relevance
“…China and India's rapid economic growth is attributed to manufacturing-led development strategies and innovation initiatives (Altenburg, Schmitz, and Stamm 2008;Hong et al 2016). The intensive development of private firms through a deepening of internal innovation capabilities fuels economic growth in China and other developing countries (Wang et al 2018). However, development strategies and innovation types differ between these two countries, as do financial markets and firms' operation decisions (Bruche 2009;Quazi and Tandon 2011).…”
Section: Some Notes On China and Indiamentioning
confidence: 99%
“…China and India's rapid economic growth is attributed to manufacturing-led development strategies and innovation initiatives (Altenburg, Schmitz, and Stamm 2008;Hong et al 2016). The intensive development of private firms through a deepening of internal innovation capabilities fuels economic growth in China and other developing countries (Wang et al 2018). However, development strategies and innovation types differ between these two countries, as do financial markets and firms' operation decisions (Bruche 2009;Quazi and Tandon 2011).…”
Section: Some Notes On China and Indiamentioning
confidence: 99%
“…The relationship between SOEs and the Chinese government is closer than that between POEs and the government [33]. It is argued that close political connections can facilitate access to external innovation resources for Chinese businesses [34]. Moreover, SOEs have more advantages than POEs in promoting regional economic development and increasing employment, so they attract more subsidies from local government [17].…”
Section: H2 Lagging Government Subsidies Have a Positive Impact On Rmentioning
confidence: 99%
“…Wu [17] confirmed that the same R&D subsidies promote more external investment in POEs than in SOEs. Wang et al [34] argued that strong formal political connections reduce firm-level R&D intensity. Based on data of Chinese listed firms, Hou et al [37] found that close government-business relations hinder corporate innovation activities and reduce innovation efficiency.…”
Section: H2 Lagging Government Subsidies Have a Positive Impact On Rmentioning
confidence: 99%
“…We see political connections potentially having both positive and negative effects on radical (i.e., cutting-edge) innovations. On one hand, political connections may provide a more favorable operational environment (Peng and Luo, 2000), access to additional resources, financing, and information (Ridge et al 2017;Li et al 2018), as well as a confidence boost (Li et al 2008) to pursue risky innovative endeavors (Wang et al 2018). In contrast, political connections can backfire on firm innovation by triggering organizational inertia and a "resource curse" (You and Du, 2012;Shi and Zhu, 2014;Hou et al 2018), greater dependency on governmental interventions (Boubakri et al 2008;Marquis and Qian, 2013;Darendeli and Hill, 2016), and agency problems (Sun et al 2016;Bertrand et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we show that there are potential tradeoffs for innovation when firms engage in multiple non-market strategies (i.e., bribery), thus adding to recent research on the interplay between non-market and market strategies (Liedong et al 2017;Parnell, 2018). Finally, from an empirical standpoint, we focus our attention on a less-researched context (i.e., Eastern Europe and Central Asia) that provides an auspicious ground for examining non-market strategies at work in emerging and lessdeveloped economies (Ge et al 2017;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%